Interferensi Bahasa Betawi di Kampung Gondrong Kota Tangerang - Agus Sulaeman; Ahmad Suherman; Mutoharoh Mutoharoh (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2020)
The purpose of this study was to describe the Betawi language interference in the conversations of the people of Gondrong Village, Cipondoh, Tangerang City. The research method used is descriptive qualitative. The data in this study were from the spoken language of the native speakers in Gondrong Village, Tangerang City. Determination of the research area is determined based on the location where the researcher lives. The informants of this study, namely: native speakers of the studied language, had no abnormalities in pronunciation, and had good memory. The instrument in this study was the researcher himself assisted by morphological interference tables and phonological structure tables. This study uses interview techniques, namely conversations are analyzed by paying attention to each word. Data recorded, listened to, and recorded. This is to complement the collected data. Data analysis used the match and divide method with various techniques adapted to the character of the data obtained and the research objectives. Next, words that show signs of morphological and phonological interference are highlighted and recorded, then the correctness of the words is checked using the Big Indonesian Dictionary. The results showed that the people of Gondrong Village conducted morphological interference in the Betawi language in their daily dialogues. The forms of interference contained in the dialogue are words and affixes (affixes). The form of affix that is inferenced is the form of prefix, suffix, and confix, while the interference in the infix form is not found.